PERILAKU MEMBACA SISWA SMA NEGERI 1 TAKALAR - St Shofiyah; Beddu Lahi; Muh Zulkifli Tahir (Jurnal Ilmiah Pranata Edu, 2019)
This research aims to examine the reading behavior of Takalar 1 High School students by using the information selection process analyst . The research was conducted because it was motivated by the low level of literacy in Indonesian society , including in Takalar District in the midst of the huge penetration of information technology . Research carried out by using a qualitative narrative method . Informants from the group of students is determined by random stratification , while the informant of the group of employees of the library is determined based on criteria specified . Results of the study showed that the behavior of reading students SMA Negeri 1 Takalar not support to the direction of the acceleration of literacy because they are actively doing the selection of the information that is up to him . Selection of these include selective exposure , selective attention , and selective retention . Selection is done based on the needs of affective , needs the integration of social , and needs escapist. Suggested perform interference to evoke the need cognitive them in order to conduct read them not just read for the need to look for entertainment and fun self